Coitus and Consequences in the Legal System: An Experimental Study - Hersch, Joni (2015)
Scholars have found that men who physically harm their intimate partners receive less punishment than men who harm strangers. In other words, in the criminal setting, coitus has consequences. In particular, for female victims, the consequence is often a legal system that offers little or no protection. Until the experimental study presented here, no one has asked whether the same is true in civil actions. This original experimental survey, fielded on eight hundred participants, provides the first-ever evidence on whether legal decision makers hold sexual activity against females in civil settings. Participants received four scenarios- a homicide, a workplace sexual harassment, a long-term business relationship, and a short-term joint venture-with randomized information about prior sexual activity between the parties. As in the criminal setting, the results show that the taint of a sexual relationship hurts women, even in civil lawsuits. Yet, the results also show that evidence of sexual activity did not hurt the female complainant in the sexual harassment scenario and it actually increased the male killer's liability in the homicide scenario. The results also suggested that male jurors may be more influenced by evidence of a female's sexual activity than are female jurors. Based on these findings, attorneys might fear less that a nuts and sluts defense will derail a sexual harassment action; but attorneys might continue to fear that a female plaintiffs sexual activity could defeat her claim in a business setting. This original experimental survey, fielded on eight hundred participants, provides the first-ever evidence on whether legal decision makers hold sexual activity against females in civil settings. Participants received four scenarios- a homicide, a workplace sexual harassment, a long-term business relationship, and a short-term joint venture-with randomized information about prior sexual activity between the parties. As in the criminal setting, the results show that the taint of a sexual relationship hurts women, even in civil lawsuits. Yet, the results also show that evidence of sexual activity did not hurt the female complainant in the sexual harassment scenario and it actually increased the male killer's liability in the homicide scenario. The results also suggested that male jurors may be more influenced by evidence of a female's sexual activity than are female jurors. Based on these findings, attorneys might fear less that a nuts and sluts defense will derail a sexual harassment action; but attorneys might continue to fear that a female plaintiff's sexual activity could defeat her claim in a business setting